THE APPLICABILITY OF ARTIFICIAL INTELLIGENCE (AI) IN DISTANCE EDUCATION (DE) - Holtz, Marcelo Martins (Seven Editora, 2026)
With the current technological demand, it is essential to use available resources in all areas, with applicability in the pedagogical scope being the focus of this present work. That said, “Artificial Intelligence” (AI) appears to be an important tool that enables the generation of intelligent devices, machinery and instruments, capable of optimizing pedagogical dynamics in a significant way, with a focus on Distance Education (EaD), consisting of the learning process mediated by information and communication technologies. The main objective of this study is to understand the concepts of Artificial Intelligence (AI) and Distance Education (EaD), which together become strong allies in this current educational context. For the development of the work, qualitative bibliographical research was carried out on academic materials, where the main advantage can be analyzed as the flexibility in the delivery of personalized knowledge to the student. On the other hand, when analyzing the disadvantages that may relate to this topic, it is possible to verify the risk of AI algorithmic bias, which occurs when an AI system produces biased and discriminatory results. Still in this direction, the reality faced in terms of low investments in this technological arrangement, which encompass AI and distance learning technologies, is a challenge, which can lead to failed results and hinder the intended success. In this sense, it is concluded that by strengthening the financial resources applied to the area, the applicability of the technologies could mean tangible results in terms of optimizing pedagogical provision.